Self-Sustainable Vacation House on Kosmaj - Pavlović, Jelena (Arhitektura i urbanizam, 2025)
The completed building is positioned near the very edge of the Kosmaj Region of Exceptional Features in the proximity of Belgrade, surrounded by a natural landscape characterized by forest areas, gentle slopes, and autochthonous vegetation, which highlights the need for a harmonious integration of the architectural design in order to minimize disruption of the environmental context. The site includes facilities intended for occasional stays, rest, and recreation for a family of five, with the main residential building being the subject of this paper. The traditional architecture of Šumadija served as inspiration for the contemporary interpretation of the timber-frame (bondruk) construction that was incorporated in the design of this two-story vacation house. The paper is an analytical presentation of the building, providing detailed explanations of the design motifs, conceptual starting points, and criteria that shaped the architectural form and programmatic structure. The primary focus is on examining the structural solutions applied, as well as the materialization, and integrated technological systems, with a consideration of how these elements contribute to functionality, aesthetic expression, and sustainability. The aim of the paper is to offer insight into the design and construction of the house, highlighting the interrelation between the conceptual and technical decisions that define the final character of the architecture. The fundamental premise of the design approach was shaped by the investor’s requirement for complete independence from the municipal supply systems, while maximizing sustainability, and maintaining a high level of comfort. In this sense, the building is self-sufficient primarily in terms of energy autonomy and the use of solar energy to meet its energy needs, as well as having its own water supply and wastewater management. However, reducing the concept to such an interpretation would significantly underestimate its scope. Therefore, the paper examines the notions of ecological and cultural sustainability, as well as their interpretations within architectural discourse, in order to establish a more precise interpretation.